HIV/AIDS be safe not sorry - Singapore. Maritim Academy (Singapore : R & D Centre, Singapore Maritime Academy, Singapore Polytechnic, 2004)
This training programme aims to raise the level of awareness of HIV/AIDS among seafarers in the Asia Pacific region. This in turn will help prevent the spread of HIV infection in this region
System requirements: Windows 9X, NT, 2000 and XP; Pentium II 266 or above; 300 MB hard disk space; 128 MB RAM; 800 x 600 monitor resolution with minimum 16K colour display; 16 bit Sound Blaster or compatible; 24x CD-ROM speed; Mouse; Speakers or headphones; Printer.
Keywords: HIV infections; AIDS (Disease).